A comprehensive insight into Lean management: Literature review and trends - Neena Sinha; Misha Matharu (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: Lean Management has evolved into an inter-disciplinary subject with linkages to Operations Management, Organizational Behaviour, and Strategic Management. The objective of this paper is to review journal articles on lean published in major academic sources with a view to provide taxonomy of the field of lean management facilitating identification of the pertinent themes that exists in literature, while presenting an overview of the main definitions, chronological evolution, diffusion among developed and emerging economies Design/methodology/approach: A review of literature has been conducted which includes 447 research articles in 51 Journals from Academic sources: Emerald Insight, T&F and Science Direct with main focus on lean management. Findings: An analysis of the surveyed literature brings to light an exponential increase in number of papers in the last 3 decades. The paper conducted study of lean in 3 phases i.e. Pre 2001, 2001-2010, Post 2010; enabling the study of maturity of lean. Observation regarding diffusion of lean globally reveals that lean has been adopted by both developed and emerging economies with noteworthy tilt towards its adoption in Asian countries in the recent past whereas initially it was confined to developed countries. New themes that have emerged such as Industry 4.0 and sustainability in the context of lean have been identified. Research limitations/implications: The aim of the paper is succinct representation of the current status and facilitating future research in the field. Originality/value: The present business environment with its rapid changes in market, rise in its economic, technical, and socio-psychological complexities has paved way for acceptance of lean as an operating strategy in a pervasive manner. The present study extends efforts of previous studies to analyse diffusion of lean globally, themes that have emerged and also includes more contemporary research with focus on its spread to emerging economies.
Keywords: 650; Lean management; literature review; emerging economies; Asian context; lean diffusion